RACE: The Theory of Emergence for Strategic Entrepreneurship - Muthuveloo, Rajendran; Ping, Teoh Ai (International Review of Management and Marketing, 2017)
This paper discusses the theory of emergence for strategic entrepreneurship, RACE. It explains the importance of contemplation in developing entrepreneurship among leaders, which would be crucial in attaining strategic agility that is needed for organizational sustainability. One of the difficulties in developing entrepreneurship is due to inability to breakthrough from social needs to self-esteem needs. RACE highlights that contemplation enable individuals to fulfill their self-esteem needs and move towards operating from super conscious mind which enables creativity. Creativity is the link between superconscious mind and universal energy. Through this link, individuals would be able to discover and recover novel ideas that will be beneficial for human kind and crucial for organizational sustainability. Keywords: Theory; Entrepreneurship; Emergence; Contemplation; Creativity; Entrepreneurial; Strategic Agility. JEL Classification: M130